Role of organizational culture in promoting employee development: a review of literature - Khan, Sadaf; Mishra, Shikha; Ansari, S. A. (Linguistics and Culture Review, 2021)
The review paper attempts a review and summarization of the existing literature available on organizational culture and employee development. Employee development is seen as an asset for the organizations, which arises from within the organization and is build by the organizational culture. The paper has shown that a positive and direct relationship exists between organizational culture and development of an employee. Employee development is dependent on the culture of the organization and that organizational culture is instrumental in building mental health of the employees.